The structure, process and outcomes of interprofessional care among knee osteoarthritis patients: a scoping review - Jessica Hiu Toon Lee; Mandy Ming Pui Kan; Arkers Kwan Ching Wong (EFORT Open Reviews)
Knee osteoarthritis (OA) is a common chronic condition that leads to joint pain and disability among older adults. An interprofessional collaborative approach has nowadays been widely advocated in knee OA management although little is known about the characteristics of care, roles and responsibilities of healthcare providers and how they collaborate as a team to optimise treatment outcomes. The Donabedian structure–process–outcome framework was used in the review. Six databases were searched from February 2013 to March 2023. A total of 26 articles that met our inclusion criteria were reported. All studies (n = 26) identified the physiotherapist as a critical member of the interprofessional team. Several studies (n = 5) have offered training to healthcare providers in the management of knee OA. The intervention components in most studies included disease-based education (n = 21) and exercise therapy (n = 16). A comprehensive understanding of the existing interprofessional knee OA care in this review could potentially assist the government and healthcare organisations in developing interprofessional practice guidelines and designing intervention programmes that maximise their benefits.